1977
DOI: 10.1136/hrt.39.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of quantitative analysis of ST slope during exercise.

Abstract: The diagnostic performance of automatic analysis of the exercise electrocardiogram in detecting ischaemic heart disease was studied in 147

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Ascoop et al [13]found that a linear combination of ST segment slope (≤180 mVs –1 measured 10–50 ms after the J point in lead CM5, and ≤190 mVs –1 in lead CC5) and ST segment depression (>0.154 and >0.200 mV, respectively, 10 ms after the J point) is the optimal criterion in the diagnosis of coronary artery disease. In this early study the investigators only used two bipolar chest electrodes and all subjects were male.…”
Section: Discussionmentioning
confidence: 99%
“…Ascoop et al [13]found that a linear combination of ST segment slope (≤180 mVs –1 measured 10–50 ms after the J point in lead CM5, and ≤190 mVs –1 in lead CC5) and ST segment depression (>0.154 and >0.200 mV, respectively, 10 ms after the J point) is the optimal criterion in the diagnosis of coronary artery disease. In this early study the investigators only used two bipolar chest electrodes and all subjects were male.…”
Section: Discussionmentioning
confidence: 99%
“…The phaseless filter system can also be recommended from the standpoint of cost performance. Ascoop et al 1977). Most of them used the onset of the QRS complex as a base point to recognize the signal, with subsequent identification of the ST segment.…”
Section: Discussionmentioning
confidence: 99%
“…Such ECGs often show a large amount of baseline wander, due to the trunk movement of the subject, as well as an alternating noise level due to myopotentials generated by the alternately active muscles in the thorax area. The observed registrations are obtained either from differential lead CC5 or from CM5 (6). Signal epochs, containing aberrancies, ST-segment depressions and much baseline wander were included in this study.…”
Section: Methodsmentioning
confidence: 99%